Iron-overload decreases Cav1.3-dependent L-type Ca(2+) currents leading to bradycardia, altered electrical conduction and atrial fibrillation - Rose, Robert A. (2011)
BACKGROUND: Chronic iron-overload (CIO) is associated with blood disorders such as thalassemias and hemochromatosis. A major prognostic indicator of survival in patients with CIO is iron-mediated cardiomyopathy, characterized by contractile dysfunction and electrical disturbances including slow heart rate (HR; bradycardia) and heart block. METHODS AND RESULTS: We have used a mouse model of CIO to investigate the effects of iron on sinoatrial node (SAN) function. As in humans, CIO reduced HR (~20%) in conscious mice as well as in anesthetized mice with autonomic nervous system blockade and in isolated Langendorff-perfused mouse hearts, suggesting bradycardia originates from altered intrinsic SAN pacemaker function. Indeed, spontaneous action potential frequencies in SAN myocytes with CIO were reduced in association with decreased L-type Ca(2+) current (I(Ca,L)) densities and positive (rightward) voltage shifts in I(Ca,L) activation. Pacemaker current (I(f)) current was not affected by CIO. Since I(Ca,L) in SAN myocytes (as well as in atrial and conducting system myocytes) activates at relatively negative potentials due to the presence of Ca(V)1.3 channels (in addition to Ca(V)1.2 channels), our data suggest that elevated iron preferentially suppresses Ca(V)1.3 channel function. Consistent with this suggestion, CIO reduced Ca(V)1.3 mRNA levels by ~40% in atrial tissue (containing SAN) and did not lower HR in Ca(V)1.3 knockout mice. CIO also induced PR interval prolongation, heart block, and atrial fibrillation, conditions also seen in Ca(V)1.3 knockout mice. CONCLUSION: Our results demonstrate that CIO selectively reduces Ca(V)1.3-mediated I(Ca,L) leading to bradycardia, slowing of electrical conduction and atrial fibrillation as seen in iron-overload patients.